Communication Strategy for Breastfeeding Mothers in Stunting Prevention in Banyumas - Nurcandrani, Prita Suci; Andhriany, Sefy (Komunikator, 2020)
Stunting could have a major bad impact on the quality of Indonesia’s human resources in the future, and startlingly in the North Purwokerto Sub-district, Banyumas Regency, it reached 261 cases in 2019. This study aimed to analyze the communication strategy carried out by the Kasih Jeruk Purut Program on breastfeeding mothers as an effort to prevent stunting in that sub-district. This study used qualitative research methods, and data were drawn by observation, in-depth interviews, and review of documentation. The results showed that this phenomenon was caused by a lack of support from the family, minimum cross-sectoral integrity cooperation, and limited understanding of breastfeeding mothers regarding the concept of breastfeeding management. There was also identified that some of the cadres did not fully understand the concept of effective communication.